2019
DOI: 10.1002/eji.201847830
|View full text |Cite
|
Sign up to set email alerts
|

Mannan‐binding lectin attenuates acetaminophen‐induced hepatotoxicity by regulating CYP2E1 expression via ROS‐dependent JNK/SP1 pathway

Abstract: Mannan‐binding lectin (MBL) acts as a soluble pattern recognition molecule in the innate immune system, which is primarily produced by the liver. MBL deficiency occurs with high frequency in the population and is reported to be associated with susceptibility to several liver diseases. In the present study, we investigated the pathophysiological role of MBL in acetaminophen (APAP)‐induced hepatotoxicity. After APAP treatment, MBL‐deficient (MBL−/−) mice had significantly higher mortality and aggravated hepatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
(61 reference statements)
0
7
0
Order By: Relevance
“…JNK and ERK MAPKs are vital intracellular signaling pathways that are responsible for apoptosis, inflammation, and proliferation ( 25 ). Activation of MAPKs is a necessary condition for APAP-induced hepatocyte death due to its amplification of mitochondrial oxidative stress and downstream transduction of the MAPK signaling pathway ( 26 , 27 ). Previous studies have indicated that JNK inhibitors or ERK1/2 inhibitors protect against APAP hepatotoxicity ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…JNK and ERK MAPKs are vital intracellular signaling pathways that are responsible for apoptosis, inflammation, and proliferation ( 25 ). Activation of MAPKs is a necessary condition for APAP-induced hepatocyte death due to its amplification of mitochondrial oxidative stress and downstream transduction of the MAPK signaling pathway ( 26 , 27 ). Previous studies have indicated that JNK inhibitors or ERK1/2 inhibitors protect against APAP hepatotoxicity ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocyte death caused by APAP hepatotoxicity is a complex process mediated by the coordination of multiple intracellular signal transduction pathways ( 1 , 27 ). A variety of apoptosis-related pathways, such as the AMPK-dependent pathway and SIRT1 pathway, are known to participate in this process.…”
Section: Discussionmentioning
confidence: 99%
“…[75,76] Genetic ablation of MBL has been shown to result in excessive ROS production and activation of JNK. [77] The activation of JNK is caused by the mitochondrial ROS generation, reportedly resulting from acetaminophen (APAP)-induced hepatic GSH depletion. [78,79] JNK-activation induced specificity protein 1 (SP1) phosphorylation which could lead to an enhanced ability of SP1 to bind to the CYP2E1 promoter after APAP attack.…”
Section: Cell Death Arising From Regulation Of Signaling Pathwaysmentioning
confidence: 99%
“…Also, attenuated activities of ALT and LDH were found in sera obtained from E2-injected fat-1 mice compared to those from WT counterparts after the APAP challenge (Figures 2(b) and 2(c) ). Moreover, we evaluated the effect of estrogen on n-3 PUFA-mediated regulation of APAP toxicity in human HepaRG cells, a reliable model to study mechanisms of APAP hepatotoxicity in humans [ 27 ]. The result showed that DHA alone accelerated APAP-induced cell death, but DHA plus estrogen treatment strongly attenuated the APAP hepatotoxicity ( Figure 2(d) ).…”
Section: Resultsmentioning
confidence: 99%